KOLABORASI KUALITAS PRODUK DAN STORE ATMOSPHERE DALAM MENINGKATKAN KEPUTUSAN PEMBELIAN PADA KULINER MIE DI JEMBER - Zahruna, Ulfi; Putri, Risma Nur Ariyana; Subawe, Imam; Hasani, Mohammad Rohib; Apriyansah, Noval Dias; Qomariyah, Nurul (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
Currently, culinary development is experiencing a period where Indonesian people are busy looking for new culinary with new names and also appetizing tastes. Culinary names are made that can make consumers interested and curious about the culinary products. Noodles are a culinary that is currently still the choice for people to meet their food needs. One of the goals of culinary is to make the name and taste as attractive as possible to attract tourists both domestically and abroad. The culinary industry continues to grow and develop in several cities in Indonesia, including Jember Regency. This study aims to determine the effect of product quality and store atmosphere on purchasing decisions at Mie XYZ Jember. This study is a quantitative study with a research population of Mie XYZ Jember consumers. The sample in this study amounted to 30 people. The data collection method used in this study was by distributing questionnaires online. Data analysis uses descriptive statistics and inductive statistics. After being analyzed, this study resulted in the product quality of Mie XYZ Jember being able to increase purchasing decisions by consumers. The next result is that the situation of the dining place or store atmosphere at Mie XYZ Jember also has a positive impact on increasing purchasing decisions. The results of this study have implications for developments related to purchasing decisions that can increase due to product quality and the resulting good store atmosphere.